Preparation method and application of ruthenium-loaded iron single atom-modified porous carbon nanotubes
By preparing oxygen-coordinated single-atom iron sites on porous carbon nanotubes and supporting ruthenium clusters, the problem of insufficient activity and stability of ruthenium-based catalysts is solved, and efficient HER catalytic performance in acidic and alkaline environments is achieved.
Patent Information
- Application Number
- CN202211304639.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-24
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-10-24
AI Technical Summary
In the prior art, the intrinsic activity of the ruthenium-based catalyst is low, and irreversible agglomeration and structural collapse are prone to occur during the catalysis process, resulting in a decrease in HER performance.
Through the iron-induced functionalization strategy, porous carbon nanotubes (CNT-V-Fe) modified with oxygen-coordinated single-atom iron site (Fe-O4) were prepared and used as a carrier to load ruthenium clusters (CNT-V-Fe) -Ru) to improve the activity and stability of the catalyst.
The HER activity of the ruthenium-based catalyst in acidic and alkaline environments is significantly improved, the stability of the catalyst is enhanced, and the Ru cluster has high dispersion and strong growth sites on CNT-V-Fe-Ru.
Smart Images

Figure CN115786972B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemistry, and in particular to a preparation method and application of ruthenium-loaded iron single atom-modified porous carbon nanotubes. Background Art
[0002] Electrochemical methods for obtaining hydrogen molecules from water molecules have become a key component of future clean energy technologies. Efficient and low-cost hydrogen evolution catalysts are crucial to the rapid development of water splitting hydrogen production technology driven by renewable electricity. To date, Pt-based catalysts have shown the best HER performance, but their scarce reserves and high price have largely limited their large-scale commercial application. Ruthenium-based materials not only have similar physical and chemical properties to platinum, but also have highly adjustable electronic structures. Therefore, they can be used as potential alternatives to platinum-based materials. Relatively low-cost ruthenium-based materials have attracted widespread attention. However, there are still major challenges in how to effectively improve the intrinsic activity of ruthenium-based catalysts. In particular, the high binding energy of Ru often leads to irreversible agglomeration and structural collapse during the catalytic process. In addition, the H adsorption strength of Ru sites is too strong, which hinders the desorption step, resulting in a decrease in HER performance.
[0003] Carbon materials have excellent electrical conductivity, large specific surface area and highly tunable structural characteristics, and have been widely used in the preparation of electrocatalysts. In addition, the introduction of porous structures and heteroatoms (N, P, O, etc.) into carbon materials can effectively increase the number of vacancy defects, thereby fixing highly dispersed active sites. However, the idea of fully regulating the electronic structure of the metal-substrate interface through achievable regulation strategies at the atomic level remains a considerable challenge. In recent years, some literature has reported the synergistic enhancement of electrocatalytic performance by platinum group metal nanoparticles supported on single-atom modified carriers. However, the explanation of the interface interaction mechanism between single-atom sites on the substrate and metal active sites is not in-depth enough, and the understanding of the effect of defects on intrinsic activity has rarely been confirmed in previous studies. Summary of the invention
[0004] The invention provides a preparation method of ruthenium-loaded iron single atom-modified porous carbon nanotubes and application thereof, which solves the problems of expensive catalytic materials and poor performance in the prior art.
[0005] In order to solve this technical problem, the present invention provides the following technical solution:
[0006] The method for preparing ruthenium-loaded iron single atom-modified porous carbon nanotubes comprises the following steps:
[0007] S1, completely dissolving Fe(NO3)3 into an ethanol solution under stirring, then adding multi-walled carbon nanotubes to the above solution under ultrasonic treatment; then, adding ammonia water to the mixture, and then heating, stirring and drying in a water bath, the obtained powder is recorded as CNT-Fe-OH;
[0008] S2, CNT-Fe-OH was heated at high temperature in air, and the obtained sample was recorded as CNT-V-Fe-Fe2O3;
[0009] S3, dispersing CNT-V-Fe-Fe2O3 in concentrated hydrochloric acid, pouring the mixture into a stainless steel high-temperature reactor lined with polytetrafluoroethylene, and heating in an oven to remove Fe2O3; after the oven is cooled to room temperature, washing with deionized water and ethanol respectively, centrifuging, and drying to obtain CNT-V-Fe;
[0010] S4, CNT-V-Fe and RuCl3·3H2O are dispersed in a solution consisting of distilled water, isopropanol and Nafion binder, ultrasonically treated, and then the dispersion is dropped onto the surface of the glassy carbon electrode; after natural drying, the electrode material is linearly scanned in the potential range of 0.1 to -0.4 V vs. RHE to prepare CNT-V-Fe-Ru.
[0011] Preferably, in step S1, the Fe(NO3)3 and ethanol solution are calculated at a molar mmol / volume ml ratio of 1:150; the multi-walled carbon nanotubes and ethanol solution are calculated at a mass mg / volume mL ratio of 20:3; and the volume ratio of ammonia water to ethanol is 1:15.
[0012] Preferably, the water bath temperature in step S1 is 60°C.
[0013] Preferably, in step S2, the high temperature heating temperature is 490° C., the heating rate is 10° C. / min, and the heating maintenance time at 490° C. is 60 min.
[0014] Preferably, the concentration of concentrated hydrochloric acid in step S3 is 36-38wt.%, and the dosage is 10ml; the heating temperature in the oven is 120°C, the heating time is 2h, and the drying temperature is 60°C.
[0015] Preferably, the step S4 is specifically as follows: 2 mg CNT-V-Fe and 0.009 mmol RuCl3·3H2O are dispersed in a solution consisting of 200 μL distilled water, 100 μL isopropanol and 20 μL 5wt.% Nafion binder, ultrasonically treated for 30 min, and then 4 μL of the dispersion is dropped onto the surface of the glassy carbon electrode; after natural drying, the electrode material is linearly scanned in the potential range of 0.1 to -0.4 V based on the reversible hydrogen electrode RHE to prepare CNT-V-Fe-Ru.
[0016] The present scheme also provides a ruthenium-loaded iron single atom modified porous carbon nanotube hydrogen evolution electrode, which is prepared by the above-mentioned preparation method.
[0017] This solution also provides the application of the above-mentioned electrode in hydrogen evolution.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] This scheme proposes an iron-induced functionalization strategy to prepare oxygen-coordinated single-atom iron sites (Fe-O4) modified, vacancy-rich carbon nanotubes (CNT-V-Fe), which are used as carbon-based carriers to load ruthenium clusters (CNT-V-Fe-Ru). The HER activity of this composite catalyst in both acidic and alkaline environments is significantly improved. CNT-V-Fe can serve as a unique carrier to strongly anchor ruthenium clusters and greatly improve catalytic stability.
[0020] This scheme highlights the characteristics of defective single-atom support materials, which can effectively regulate the interfacial electronic structure, especially at the metal-substrate interface. The electronic structure of the metal active sites can be effectively regulated through interfacial interactions with the substrate. Regulating the binding part of the metal-substrate interface will fundamentally solve the challenges faced by ruthenium and other transition metal-based catalysts, which is beneficial to the activity and stability of the electrocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0022] Figure 1 The preparation process of CNT-V-Fe and CNT-V-Fe-Ru, and the schematic diagram of HER catalysis process on Ru site;
[0023] Figure 2 TG and DTG curves of CNT and CNT-Fe-OH;
[0024] Figure 3For morphology and structure characterization; among them, (a) is the SEM image of CNT-V-Fe (the inset is TEM); (b) is the HAADF-STEM image; (c) is the HRTEM image of CNT-V-Fe-Ru; (d) is the Raman spectra of CNT, CNT-Fe, CNT-V and CNT-V-Fe; (e) is the XANES of Fe foil, Fe2O3, CNT-V-Fe and CNT-V-Fe-Ru; (f) is the FT-EXAFS data, in which the intensity of the Fe foil data is halved; (g) is the XRD spectrum of CNT-V-Fe-Ru and CNT-V-Fe; (h) is the XANES of Ru foil, RuO2 and CNT-V-Fe-Ru; (i) is the FT-EXAFS data;
[0025] Figure 4 This is the SEM image of CNT-V;
[0026] Figure 5 This is the SEM image of CNT-Fe;
[0027] Figure 6 The SEM image of CNT-Fe and the element distribution map of C, O, and Fe; (a) is the SEM image of CNT-Fe; (b) is the element distribution map of C; (c) is the element distribution map of O; (d) is the element distribution map of Fe;
[0028] Figure 7 are adsorption curves and pore size distribution diagrams; wherein, (a) is the nitrogen adsorption-desorption curve (a) of CNT, CNT-Fe, CNT-V and CNT-V-Fe; (b) is the pore size distribution diagram of CNT, CNT-Fe, CNT-V and CNT-V-Fe;
[0029] Figure 8 HRTEM image of CNT-V-Fe; the inset is the corresponding FFT image;
[0030] Fig. 9 The XPS spectra of CNT-V-Fe, where (a) is the full XPS spectrum; (b) is Fe 2p; (c) is O1s XPS spectrum;
[0031] Fig.10 (a) is the optimized Fe-O4 structure; Fig.10 (b)-(d) are the experimental and fitting diagrams of CNT-V-Fe for k(b) and R(c,d) space;
[0032] Fig.11 Ru 3d XPS spectra of CNT-Ru, CNT-Fe-Ru, CNT-V-Ru and CNT-V-Fe-Ru;
[0033] Fig.12 XRD spectra of CNT-Ru, CNT-Fe-Ru, CNT-V-Ru and CNT-V-Fe-Ru;
[0034] Fig.13 This is the SEM image of CNT-Ru;
[0035] Fig.14 This is the SEM image of CNT-V-Ru;
[0036] Fig.15 This is the SEM image of CNT-Fe-Ru;
[0037] Fig.16 HER electrocatalytic performance normalized based on geometric area; (a) is the polarization curve in 0.5M H2SO4; (b) is the Tafel plot corresponding to (a); (c) is the polarization curve in 1M KOH; (d) is the Tafel plot corresponding to (c);
[0038] Fig.17 Intrinsic activity analysis of the catalyst; (a) in 0.5 M H2SO4 and (b) in 1 M KOH at -0.1 V vs RHE, the current density normalized to the ECSA of Ru and the mass loading of Ru in the sample (mass activity (MA)), and the TOF value of the sample at -0.1 V vs RHE and the corresponding exchange current density (J0); the sample in (c) 0.5 M H2SO4 and (d) 1 M KOH electrolytes at a current density of 10 mA cm geo -2 Stability test under conditions of
[0039] Fig.18 (a) is CNT-Fe, (b) is CNT-V-Fe, (c) is CNT-V, (d) is CNT-Ru, (e) is CNT-Fe-Ru, (f) is CNT-V-Ru, and (g) is a schematic diagram of the simulation of the optimized samples of CNT-V-Fe-Ru;
[0040] Fig.19 (a) Optimization of the binding energy between CNT-Ru, CNT-Fe-Ru and CNT-V-Fe-Ru substrates and Ru clusters and the charge distribution of CNT-V-Fe-Ru (inset); Fig.19 (b) Gibbs free energy diagram for H+ to H2; Fig.19 (c) is the Gibbs free energy diagram of alkaline medium; Fig.19(d) PDOS of potential active sites p and d of CNT-V-Fe, CNT-Ru, CNT-Fe-Ru, CNT-V-Fe-Ru and CNT-V-Fe-Ru containing H bonds; the corresponding optimized structure of the active site (inset on the right). Fig.19 (e) is a catalyst in an acidic medium process activation barrier, transition (TS) and final (FS) states); Fig.19 (f) Tafel activation barrier of Pt(111) (initial (IS), transition (TS) and final (FS) states); Fig.19 (g) is the sample in alkaline medium The activation barrier of the process.
[0041] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0042] Example 1
[0043] (1) Preparation of CNT-V-Fe
[0044] First, Fe(NO3)3 (0.2mmol) was completely dissolved in an ethanol solution (30mL) under stirring. Then, multi-walled carbon nanotubes (CNTs, 200mg) were added to the above solution under ultrasonic treatment. After that, ammonia water (2ml, 25wt.%) was added to the mixture, and then stirred and dried in a water bath at 60℃, and the resulting powder was CNT-Fe-OH. Next, CNT-Fe-OH was heated to 490℃ in air at a heating rate of 10℃ per minute and kept at this temperature for 60 minutes. The resulting sample was recorded as CNT-V-Fe-Fe2O3. Then, CNT-V-Fe-Fe2O3 was dispersed in concentrated hydrochloric acid (10ml, 36-38wt.%), and the mixture was poured into a stainless steel high-temperature reactor with a polytetrafluoroethylene liner (25ml), and heated at 120℃ in an oven for 2h to remove Fe2O3. After the oven was cooled to room temperature, the product was washed with deionized water and ethanol, respectively, centrifuged, and dried at 60° C. to obtain CNT-V-Fe.
[0045] (2) Preparation of CNT-V-Fe-Ru
[0046] CNT-V-Fe (2 mg) and RuCl3·3H2O (0.009 mmol) were dispersed in a solution consisting of distilled water (200 μL), isopropanol (100 μL) and Nafion binder (20 μL, 5 wt.%), and ultrasonically treated for 30 min, and then the dispersion (4 μL) was dropped onto the surface of the glassy carbon electrode. After natural drying, the electrode material was linearly scanned in the potential range of 0.1 to -0.4 V based on the reversible hydrogen electrode (RHE) to prepare CNT-V-Fe-Ru.
[0047] Comparative Example 1
[0048] The difference between this comparative example and Example 1 is that: (1) Fe(NO3)3 is not introduced to prepare CNT-V; (2) CNT-V-Ru is prepared using CNT-V as raw material.
[0049] Comparative Example 2
[0050] The difference between this comparative example and Example 1 is that: (1) CNT-Fe-OH is heated under argon flow, and other preparation conditions are the same as CNT-V-Fe to obtain CNT-Fe; (2) CNT-Fe-Ru is prepared using CNT-Fe as raw material.
[0051] Comparative Example 3
[0052] Initial CNT (2 mg) and RuCl3·3H2O (0.009 mmol) were dispersed in a solution consisting of distilled water (200 μL), isopropanol (100 μL) and Nafion binder (20 μL, 5 wt.%), ultrasonically treated for 30 min, and then the dispersion (4 μL) was dropped onto the surface of the glassy carbon electrode. After natural drying, the electrode material was linearly scanned in the potential range of 0.1 to -0.4 V based on the reversible hydrogen electrode (RHE) to prepare CNT-Ru.
[0053] Example 2
[0054] Electrochemical measurements were performed at room temperature using an electrochemical workstation (204, Autolab, Switzerland). In a three-electrode system, a carbon rod and Ag / AgCl (saturated KCl aqueous solution) electrode were used as the counter electrode and reference electrode, and a glassy carbon electrode and a catalyst supported on carbon paper were used as the working electrode. KOH (1 mol L -1 ) and H2SO4 (0.5 mol L -1 ) aqueous solution as the electrolyte. The catalysts are selected from CNT-V-Fe, CNT-V-Fe-Ru in Example 1, CNT-V-Ru in Comparative Example 1, CNT-Fe-Ru in Comparative Example 2, CNT-Ru in Comparative Example 3, and Pt / C (20%); according to the calibration equation E(vs.RHE) =E (Ag / AgCl) +0.198+0.059×pH, the potential was converted to the potential based on the reversible hydrogen electrode (RHE). The linear sweep voltammetry scan rate was 10 mV s -1 The resistance of the electrolyte and charge transfer was obtained by fitting the equivalent circuit using Nova software (1.11). Then, the iR drop of all electrochemical measurements was corrected according to the solution resistance. The electrochemical impedance spectra (EIS) of these materials were recorded in the range of 10 kHz to 0.01 Hz.
[0055] Figure 1 The preparation process of the CNT-V-Fe carrier with a large number of vacancy defects and single iron atom sites in Example 1 is demonstrated. Although carbon nanotubes (CNTs) have high thermal stability in air, metal compounds can induce local oxidation of carbon nanotubes at a temperature below the degradation temperature of pure carbon nanotubes. CNTs-Fe-OH can be obtained by loading the pore-forming agent (iron-based compound) onto CNTs. Figure 2 From the TG and DTG curves of CNTs and CNTs-Fe-OH, it can be seen that the temperature at which the mass of carbon species in CNTs-Fe-OH decreases rapidly (565°C) is significantly lower than that of CNTs (603°C), which indicates that the introduction of iron compounds reduces the thermal stability of CNTs. The carbon near the iron compound begins to degrade at 470°C, while CNTs only degrade at 510°C. The reduction in the thermal stability of local carbon species makes it possible to form a porous structure in carbon nanotubes. The relatively unstable carbon species react with oxygen to form a porous structure with vacancy defects, while the main skeleton of CNTs is retained ( Figure 3 a). Through temperature optimization, a heating temperature of 490°C was used to prepare CNT-V-Fe with rich defective porous structure.
[0056] Comparative Example 1: CNT-V is prepared without introducing an iron-based compound. The preparation process is the same as that of CNT-V-Fe except that no iron compound is introduced. CNT-V only shows a small amount of porous structure ( Figure 4 ). These results further confirm that iron compounds are effective pore-forming agents that promote the formation of defective porous structures.
[0057] In addition, Comparative Example 2 also prepared a CNT-Fe control sample by heating CNT-Fe-OH under an argon flow. CNT-Fe has a smooth surface and introduces iron sites without introducing defects ( Figure 5 , Figure 6 ad).
[0058] The formation of defective porous structure is conducive to the increase of specific surface area and the number of vacancy defects, which has a positive effect on improving reaction rate and intrinsic activity. The nitrogen adsorption-desorption curve also proves the formation of porous structure ( Figure 7 a). CNT-V-Fe has the highest specific surface area (195.2 m 2 g -1 ), significantly higher than carbon nanotubes (81.7m 2 g -1 )、CNT-Fe(82.1m 2 g -1 ) and CNT-V(116.9m 2 g -1 In addition, CNT-V-Fe also has a larger pore size distribution than CNT, CNT-Fe and CNT-V ( Figure 7 b), which indicates that there will be better mass transfer process during the electrocatalytic process.
[0059] like Figure 8 As shown in the figure, the HRTEM image and the corresponding fast Fourier transform (FFT) image of CNT-V-Fe show that the breakage of the lattice fringes and the increase of the amorphization degree can be clearly observed near the porous structure, indicating that the formation process of the porous structure is accompanied by the increase of vacancy defects and the decrease of the graphitization degree of carbon. Figure 3 d Raman spectrum shows that the intensity ratio of the D peak to the G peak of the sample is as follows from low to high: CNT (I D / I G =0.714), CNT-Fe(I D / I G =0.718), CNT-V(I D / I G =0.742), CNT-V-Fe(I D / I G =1.036. D / I G The higher the ratio, the more vacancy defects there are in CNT-V-Fe and the lower the graphitization degree of carbon, indicating that a porous structure rich in defects has been formed. More importantly, according to the SEM and TEM images of CNT-V-Fe ( Figure 3 a), the main structure of CNTs was successfully retained during the preparation process.
[0060] Spherical aberration corrected HAADF-STEM images and XPS spectra further analyzed the composition and structure of CNT-V-Fe. Figure 3b) Further showing the porous structure of CNT-V-Fe, isolated bright spots with a diameter of about 0.1 nm can be observed, indicating that isolated iron atoms are modified on CNT-V-Fe during the etching process. In addition, XPS spectra further confirm the presence of C, O and Fe in CNT-V-Fe ( Fig. 9 ac). The binding energy at 531.8 eV ( Fig. 9 The O1s XPS spectrum in c also indicates the formation of CO-Fe. However, due to the low content of Fe in CNT-V-Fe (0.15 wt. % by ICP analysis), the oxidation state and fine coordination structure of single iron atoms cannot be well confirmed by XPS analysis alone.
[0061] XAFS spectroscopy is a powerful technique for accurately analyzing the fine structure of metal centers, such as the coordination environment and chemical state. Figure 3 e shows the Fe-k-edge XANES data of CNT-V-Fe, Fe2O3, and Fe foil. The rising edge position of CNT-V-Fe at 7120.6 eV and the obvious front edge peak at 7115.6 eV are very close to Fe2O3, indicating that the oxidation state of iron is about +3. Figure 3 The Fe-kEXAFS (FT-EXAFS) data in f show that the iron atoms are mainly coordinated with O atoms (peak position is position), rather than coordinating with other Fe atoms (the Fe-Fe bond in ), which is consistent with the atomically dispersed Fe in CNT-V-Fe. The Fe-O bond in Fe2O3 At the same time, Fe2O3 The obvious peak at , indicating the Fe-Fe coordination interaction at the higher shell, while CNT-V-Fe never showed such a signal. These results further confirmed that the iron sites in the prepared catalysts are isolated single atoms rather than Fe2O3.
[0062] Based on the FT-EXAFS results, the defect-modified Fe-O4 model structure ( Fig.10 a) Fitting FT-EXAFS spectrum. Fig.10 As shown in b-10d, in k and R space, the EXAFS fitting results based on the model fit well with the experimental results.
[0063] Based on the above results, defect-rich CNTs (CNT-V-Fe) modified with single iron atoms were successfully prepared by the iron oxide-induced partial etching functionalization strategy. CNT-V-Fe with unique nanostructure and composition was used as a carrier to anchor and stabilize ruthenium clusters (CNT-V-Fe-Ru). Figure 3The SEM and TEM images of CNT-V-Fe-Ru in c show that small clusters with a diameter of 5 to 10 nm grow around the defective porous structure, and the lattice fringes of these clusters are determined to be Ru(101). In addition, the XRD spectrum ( Figure 3 g) and Ru 3d XPS spectra ( Fig.11 , about 280.6eV) all confirm that the Ru(0) clusters are successfully loaded on CNT-V-Fe. According to the Fe-k edge XANES graph of CNT-V-Fe-Ru ( Figure 3 e), the rising edge position of CNT-V-Fe-Ru at 7117.1eV and the obvious edge pre-peak at 7115.2eV are very close to CNT-V-Fe. Therefore, the oxidation state of iron in CNT-V-Fe-Ru is also about +3. Figure 3 The Fe-k-edge EXAFS data in f show that the Fe-O bond is The signal intensity of CNT-V-Fe-Ru decreases, indicating that the interaction between the iron and ruthenium sites in CNT-V-Fe-Ru reduces the Fe-O coordination number. Figure 3 h further shows the Ru-k edge XANES of CNT-V-Fe-Ru. The rising edge position and obvious edge front peak are close to the position of elemental Ru, indicating the formation of Ru clusters (0) in CNT-V-Fe-Ru. Figure 3 It can be seen that in The peaks at indicate that Ru atoms are mainly coordinated with Ru or Fe atoms (Ru-Ru or Ru-Fe). In addition, the decrease in the absorbance of the ruthenium-metal bond may be the result of the interaction between the ruthenium cluster and the substrate interface. These results reveal that an interface structure is formed between the ruthenium cluster and the CNT-V-Fe matrix through the Ru-Fe bond. According to the XPS spectra of CNT-Ru, CNT-Fe-Ru and CNT-V-Ru ( Fig.11 ) and XRD spectra ( Fig.12 ), metal Ru is also loaded on CNT, CNT-Fe and CNT-V. However, the particle diameter of Ru on CNT-Ru, CNT-Fe-Ru and CNT-V-Ru (>100nm) is much higher than that on CNT-V-Fe-Ru ( Figure 13-15 ). The abundant vacancy defects in CNT-V-Fe increase the specific surface area and provide more anchor points for the growth of Ru clusters. In addition, the electronegativity differences among C, O, and Fe and the synergistic effect of vacancy defects and oxygen-coordinated iron single atoms (Fe-O4) can induce local charge redistribution and enhance the interfacial interaction between Ru clusters and the support. These characteristics are conducive to the firm growth of Ru clusters and avoid the agglomeration of particles during the preparation process. Therefore, Ru clusters have high dispersibility on CNT-V-Fe-Ru.
[0064] In order to investigate the effects of different interface-modified substrates on the HER activity, the electrocatalytic performance of CNT-V-Fe, CNT-Ru, CNT-Fe-Ru, CNT-V-Ru, CNT-V-Fe-Ru and Pt / C (20%) in 0.5 M H2SO4 was evaluated.
[0065] like Fig.16 As shown in a, the cathode polarization current density of CNT-V-Fe is negligible. After the CNT-V-Fe and Ru clusters are combined, the current density of CNT-V-Fe-Ru increases significantly, indicating that metal Ru is an indispensable active site for HER activity. Among the catalysts based on different carbon substrates (CNT, CNT-Fe, CNT-V, and CNT-V-Fe), CNT-V-Fe-Ru has the lowest overpotential, reaching 10 mA cm geo -2 The overpotential required for the current density is 64mV, which is lower than CNT-Ru (136mV), CNT-Fe-Ru (123mV), and CNT-V-Ru (115mV), and has the best performance. According to the Tafel curve ( Fig.16 b), the Tafel slope of CNT-V-Fe-Ru is 51mVdec -1 The results show that the HER process catalyzed by CNT-V-Fe-Ru follows mechanism, The process is the rate-limiting step, which is different from the hydrogen production mechanism on Pt / C (20%) (~30mV dec -1 , Volmer-Tafel mechanism). In addition, compared with CNT-V-Fe-Ru, CNT-Ru (73mV dec -1 )、CNT-Fe-Ru(69mV dec -1 ) and CNT-V-Ru (60mV dec -1 ) has a higher Tafel slope, indicating that the cathode current density of CNT-V-Fe-Ru can increase more rapidly under the same overpotential increment.
[0066] In order to further verify the high catalytic activity of CNT-V-Fe-Ru, its HER activity in 1.0 M KOH was further studied ( Fig.16 c). As expected, CNT-V-Fe-Ru also exhibits significant HER catalytic activity at 10 mA cm geo -2 Under the condition of , the overpotential is as low as 38mV, which is comparable to Pt / C (20%) (32mV), and lower than CNT-Ru (60mV), CNT-Fe-Ru (57mV), and CNT-V-Ru (48mV). Fig.16d shows that the Tafel slope of CNT-V-Fe-Ru is 41mV dec -1 , indicating that the same Its Tafel is slightly higher than that of Pt / C (20%) (38mV dec- 1 ), but better than CNT-Ru (57mV dec -1 )、CNT-Fe-Ru(55mV dec -1 ) and CNT-V-Ru (55mV dec -1 ). It should be noted that the HER catalytic performance of Pt / C (20%) in alkaline electrolytes is worse than that in acidic electrolytes, especially at high current density, which is mainly due to the more abundant hydrogen ions and faster kinetics in acidic media. In addition, due to the limited adsorption and dissociation of H2O by Pt-based materials, they exhibit relatively sluggish kinetics under alkaline conditions. The Ru site can promote the adsorption and dissociation process of H2O, thereby improving the catalytic performance of HER in alkaline electrolytes. At the same time, the overly strong Ru-H bond in acidic solutions will limit the overall reaction of HER, resulting in its HER performance being poorer than that in alkaline solutions.
[0067] CNT-Ru, CNT-Fe-Ru, CNT-V-Ru, and CNT-V-Fe-Ru differ significantly in composition and microstructure. Therefore, the LSVs normalized to the geometric area cannot represent the intrinsic activity. For this reason, the polarization curves were normalized to the Ru / Pt content and the ECSA of Ru / Pt obtained by underpotential deposition (UPD) of copper (ECSA Ru / Pt ) to measure the intrinsic activity. Obviously, compared with CNT-Ru, CNT-Fe-Ru and CNT-V-Ru, the mass activity and ECSA normalized current density ( Fig.17 ab) performed best. The J0 of CNT-V-Fe-Ru in acidic and alkaline electrolytes were 18.5 and 62.6 μA cm ECSA(Ru) -2 , which is higher than that of CNT-Ru, CNT-Fe-Ru and CNT-V-Ru, indicating that the HER kinetic rate of CNT-V-Fe-Ru is much faster. In addition, compared with CNT-Ru, CNT-Fe-Ru and CNT-V-Ru, CNT-V-Fe-Ru also exhibits the highest turnover frequency (TOF) ( Fig.17 ab), which further indicates that the activity of Ru on the CNT-V-Fe substrate is higher. The catalytic stability test of the catalytic material is further shown in Fig.17As shown in c-17d, CNT-V-Fe-Ru exhibits long-lasting durability with only slight changes in applied potential, and its performance is far superior to that of CNT-Ru, CNT-Fe-Ru, and CNT-V-Ru. The iron single-atom-modified defect-rich pore structure of CNT-V-Fe-Ru provides a firm growth site for the Ru clusters and enhances the interaction at the Ru cluster-substrate interface, resulting in high structural and catalytic stability.
[0068] In order to further understand the fundamental reason why CNT-V-Fe-Ru achieves efficient HER catalytic performance, density functional theory (DFT) calculations were performed. Fig.18 (a) CNT-Fe, Fig.17 (b) CNT-V-Fe, Fig.17 (c) CNT-V, Fig.18 (d) CNT-Ru, Fig.18 (e) CNT-Fe-Ru, Fig.18 (f) CNT-V-Ru, Fig.18 (g) The bond energy between the CNT-V-Fe-Ru) modified substrates is as follows Fig.18 a. The order of bond energy is: CNT-V-Fe-Ru (4.82 eV) > CNT-V-Ru (4.22 eV) > CNT-Fe-Ru (3.11 eV) > CNT-Ru (1.62 eV). In different models, the bond energy between CNT-V-Fe-Ru and Ru clusters is the highest. That is, Ru sites may be preferentially deposited on defective Fe-O4 groups to form atomic and defect interfaces between Ru clusters and CNT-V-Fe carriers. In addition, these features can greatly enhance the stability of ruthenium clusters. Therefore, CNT-V-Fe-Ru has higher HER catalytic stability than CNT-Ru, CNT-Fe-Ru and CNT-V-Ru. According to the charge distribution of CNT-V-Fe-Ru after optimization ( Fig.19 a inset), due to the redistribution of charge between the CNT-V-Fe matrix and the Ru clusters, the Ru sites become effective active centers, which is beneficial to optimize the adsorption of hydrogen and water ( Fig.19 b-19c). Fig.19 d The partial density of states (PDOS) of potential active sites (Ru or Fe) after H adsorption in CNT-V-Fe, CNT-Ru, CNT-Fe-Ru, CNT-V-Ru, and CNT-V-Fe-Ru were further compared. For CNT-V-Fe, Fe-d exhibits a low electron density (E f ). However, CNT-Ru, CNT-Fe-Ru, CNT-V-Ru and CNT-V-Fe-Ru have fThe electron density of Ru-d nearby is significantly enhanced, indicating that Ru is a potential active center for HER. However, the adsorption intensity of H on the Ru site is too strong. In order to improve the catalytic performance, it is necessary to moderately weaken the adsorption intensity of H on the Ru site by introducing a carrier. After adsorbing H, the d centers of CNT-Ru, CNT-Fe-Ru, CNT-V-Ru and CNT-V-Fe-Ru are -1.68eV, -1.77eV, -1.72eV and -1.84eV, respectively. According to the d-band theory, the adsorption intensity of H at the Ru site of the CNT-V-Fe substrate is weakened the most. Therefore, CNT-V-Fe-Ru has better HER catalytic performance. To confirm this hypothesis, Fig.19 b Further comparison of ΔG of CNT-V-Fe, CNT-Ru, CNT-Fe-Ru, CNT-V-Fe-Ru, CNT-V-Fe-Ru, Ru(101) and Pt(111) H* ΔG of CNT-V-Fe H* >0eV(ΔG H* =0.48 eV), indicating that the adsorption strength of H is relatively low. ΔG of Ru(101) H* <0eV, the maximum |ΔG H* |Value(ΔG H* =-0.42 eV), indicating that the adsorption strength of Ru(101) to H is too strong to show high catalytic activity. However, compared with Ru(101), the introduction of CNT, CNT-Fe, CNT-V and CNT-V-Fe substrates effectively weakened the CNT-Ru (ΔG H* =-0.37eV), CNT-Fe-Ru(ΔGH*=-0.28eV), CNT-V-Ru(ΔG H* =-0.26eV) and CNT-V-Fe-Ru (ΔG H* =-0.22 eV) in the Ru site for H adsorption. The synergistic effect of vacancy defects and iron single atom sites more fully reduces the adsorption strength of Ru sites for H in CNT-V-Fe-Ru, which is consistent with the results of PDOS. In addition, the ΔG H* Very close to Pt(111)(ΔG H* =-0.21 eV), with the most advanced HER activity, in line with the Sabatier principle, i.e., the optimal hydrogen adsorption free energy (ΔG) of an ideal HER active site. H*) is close to zero. Therefore, compared with CNT-V-Fe, CNT-Ru, CNT-Fe-Ru and CNT-V-Ru, CNT-V-Fe-Ru with a defect-rich matrix modified with a single iron atom has efficient HER catalytic performance, which is confirmed by experimental data. For water reduction under alkaline conditions, the first step of HER is the adsorption and dissociation of water. The CNT-V-Fe-Ru model shows the strongest water adsorption free energy (-0.33 eV, Fig.19 c), which is extremely beneficial to the HER process. Compared with CNT-Ru, CNT-Fe-Ru, CNT-Fe-Ru and Pt(111), CNT-V-Fe-Ru has a lower ΔG = -0.17 eV in the water dissociation process, indicating that CNT-V-Fe-Ru has the smallest HER overpotential. In addition, by calculating the highest free energy of the searched transition state (TS), the activation energy barriers ( Fig.19 e-19f). Fig.16 From the Tafel slope of b, it can be seen that for acidic HER, the RDS of CNT-Ru, CNT-Fe-Ru, CNT-V-Ru and CNT-V-Fe-Ru are step, while the RDS of Pt / C is a Tafel step. Therefore, the calculated activation barrier of CNT-V-Fe-Ru is 0.59 eV ( Fig.19 e), which is lower than 0.65 eV of CNT-V-Ru, 0.72 eV of CNT-Fe-Ru and 0.93 eV of CNT-Ru, but higher than 0.39 eV of Pt(111) ( Fig.19 f) By Fig.16 The Tafel slope of the alkaline water dissociation reaction in d shows that the RDS of all ruthenium-based catalysts and Pt / C are Steps. Fig.19 As shown in Fig. g, the activation barrier of CNT-V-Fe-Ru is 0.62 eV, which is much smaller than that of CNT-V-Ru, CNT-Fe-Ru and CNT-Ru. The highest energy barrier is shown in the step, which is consistent with our experimental results. In general, DFT calculations further enhance our understanding of the interface effects of Ru cluster atoms and defects under acidic and alkaline conditions.
[0069] A unique carbon nanotube CNT-V-Fe support with abundant vacancy defects and single-atom iron sites (Fe-O4) was obtained by partial etching of carbon nanotubes induced by iron oxide. Compared with CNT, CNT-Fe and CNT-V, the defect-rich pore structure modified by single-atom iron sites in CNT-V-Fe promotes the high dispersion and firm growth of Ru clusters on the substrate through Ru-Fe bonds. Therefore, compared with CNT-Ru, CNT-Fe-Ru and CNT-V-Ru, CNT-V-Fe-Ru has lower overpotential, smaller Tafel slope, larger J0 and TOF values and more durable stability. Theoretical calculations further prove that the synergistic effect of vacancy defects and single-atom iron sites leads to higher binding energy between the CNT-V-Fe-Ru clusters and the CNT-V-Fe substrate interface. At the same time, the H adsorption strength of Ru active sites is optimized to the maximum extent, so that CNT-V-Fe-Ru has higher HER activity and durable stability. Experimental data and theoretical calculations together reveal the broad application prospects of metal single-atom modification of defect-rich substrates in the design of efficient catalytic materials. This study is an important example of using single-atom catalysts as advanced support materials, which helps to gain a deeper understanding of the interaction mechanism of the metal-matrix interface at the atomic level and provides more opportunities for expanding the application of single-atom materials.
[0070] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing ruthenium-loaded iron single atom-modified porous carbon nanotubes, characterized in that: The steps include: S1, completely dissolving Fe(NO3)3 into an ethanol solution under stirring, then adding multi-walled carbon nanotubes to the above solution under ultrasonic treatment; then, adding ammonia water to the mixture, and then heating and stirring in a water bath to evaporate to dryness, and the obtained powder is recorded as CNT-Fe-OH; S2, CNT-Fe-OH was heated at high temperature in air, and the obtained sample was recorded as CNT-V-Fe-Fe2O3; the high temperature heating temperature was 490°C, the heating rate was 10°C / min, and the heating time at 490°C was 60min; S3, dispersing CNT-V-Fe-Fe2O3 in concentrated hydrochloric acid, pouring the mixture into a stainless steel high-temperature reactor lined with polytetrafluoroethylene, and heating in an oven to remove Fe2O3; after the oven is cooled to room temperature, washing with deionized water and ethanol respectively, centrifuging, and drying to obtain CNT-V-Fe; S4, CNT-V-Fe and RuCl3·3H2O are dispersed in a solution consisting of distilled water, isopropanol and Nafion binder, ultrasonically treated, and then the dispersion is dropped onto the surface of the glassy carbon electrode; after natural drying, the electrode material is linearly scanned in the potential range of 0.1 to -0.4 V vs. RHE to prepare CNT-V-Fe-Ru.
2. The method for preparing ruthenium-loaded iron single atom-modified porous carbon nanotubes according to claim 1, characterized in that: In the step S1, Fe(NO3)3 and ethanol solution are calculated at a molar mmol to volume ml ratio of 1:150; multi-walled carbon nanotubes and ethanol solution are calculated at a mass mg to volume mL ratio of 20:3; and the volume ratio of ammonia water to ethanol is 1:
15.
3. The method for preparing ruthenium-loaded iron single atom-modified porous carbon nanotubes according to claim 1, characterized in that: The water bath temperature in step S1 is 60°C.
4. The method for preparing ruthenium-loaded iron single atom-modified porous carbon nanotubes according to claim 1, characterized in that: The concentration of concentrated hydrochloric acid in step S3 is 36-38wt.%, and the dosage is 10ml; the heating temperature in the oven is 120°C, the heating time is 2h, and the drying temperature is 60°C.
5. The method for preparing ruthenium-loaded iron single atom-modified porous carbon nanotubes according to claim 1, characterized in that: The step S4 is specifically as follows: 2 mg CNT-V-Fe and 0.009 mmol RuCl3·3H2O are dispersed in a solution consisting of 200 μL distilled water, 100 μL isopropanol and 20 μL 5 wt.% Nafion binder, ultrasonically treated for 30 minutes, and then 4 μL of the dispersion is dropped onto the surface of the glassy carbon electrode; after natural drying, the electrode material is linearly scanned in the potential range of 0.1 to -0.4 V based on the reversible hydrogen electrode RHE to prepare CNT-V-Fe-Ru.
6. A ruthenium-loaded iron single atom modified porous carbon nanotube hydrogen evolution electrode, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the electrode according to claim 6 in hydrogen evolution.
Citation Information
Patent Citations
Iron-doped defect-rich carbon nitride nanotube photocatalyst and preparation method and application thereof
CN112742435A
Three-dimensional carbon nanotube loaded ruthenium-based catalyst as well as preparation method and application thereof
CN114657590A